Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve the expression and find the value of x.
[tex] \frac{x + 1}{10} - \frac{3(x - 1)}{5} = 2 [/tex]


Sagot :

[tex]\large\underline{\sf{Solution-}}[/tex]

[tex]\sf \dfrac{x + 1}{10} - \dfrac{3(x - 1)}{5} = 2[/tex]

[tex]\sf\longmapsto \dfrac{x + 1}{10} - \dfrac{3x - 3}{5} = 2[/tex]

[tex]\sf\longmapsto \dfrac{(x + 1) - 2(3x - 3)}{10} = 2[/tex]

[tex]\sf\longmapsto \dfrac{x + 1 - (6x - 6)}{10} = 2[/tex]

[tex]\sf\longmapsto \dfrac{x + 1 - 6x + 6}{10} = 2[/tex]

[tex]\sf\longmapsto \dfrac{ - 5x + 7}{10} = 2[/tex]

[tex]\sf\longmapsto - 5x + 7 = 20[/tex]

[tex]\sf\longmapsto - 5x = 20 - 7[/tex]

[tex]\sf\longmapsto - 5x = 13[/tex]

[tex]\sf\therefore x = - \dfrac{13}{5} [/tex]

Hence, the value of x will be -13/5 respectively.

[tex] \huge \boxed{\mathfrak{Question} \downarrow}[/tex]

[tex]\frac{x + 1}{10} - \frac{3(x - 1)}{5} = 2 \\ [/tex]

[tex] \large \boxed{\mathfrak{Answer \: with \: Explanation} \downarrow}[/tex]

[tex]\frac { x + 1 } { 10 } - \frac { 3 ( x - 1 ) } { 5 } = 2 \\ \frac { x + 1 } { 10 } - \frac { 3 ( x - 1 ) } { 5 } = \frac{2}{1} [/tex]

Take a look at the denominators. The denominators are 10, 5 & 1. Their LCM is 10. So, multiply the fractions on both the sides of the equation by 10.

[tex]\frac { x + 1 } { 10 } - \frac { 3 ( x - 1 ) } { 5 } = \frac{2}{1} \\ \frac{x + 1}{10} \times \frac{1}{1} - \frac{3x - 3}{5} \times \frac{2}{2} = \frac{2}{1} \times \frac{10}{10} \\ \frac{x + 1}{10} - \frac{6x - 6}{10} = \frac{20}{10} [/tex]

Now cancel the denominators (as they have the same value) & take the numerators.

[tex]x + 1 - (6x - 6) = 20 \\ [/tex]

Now, simplify it.

[tex]x + 1 - (6x - 6) = 20 \\ x + 1 - 6x + 6 = 20 \\ x - 6x + 1 + 6 = 20 \\ - 5x + 7 = 20 \\ - 5x = 13 \\ x = -\frac{13}{5} \\ \boxed{ \boxed{ \bf x = - \frac{13}{5} =\: - 2 \frac{3}{5} = - 2.6}}[/tex]

__________________

Hope it'll help you!

ℓu¢αzz ッ